1996
DOI: 10.1021/tx960054f
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Identification of Environmental Estrogens

Abstract: Comparative molecular field analysis (CoMFA), a three-dimensional quantitative structure-activity relationship (3D-QSAR) paradigm, was used to examine the estrogen receptor (ER) binding affinities of a series of structurally diverse natural, synthetic, and environmental chemicals of interest. The CoMFA/3D-QSAR model is statistically robust and internally consistent, and successfully illustrates that the overall steric and electrostatic properties of structurally diverse ligands for the estrogen receptor are bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
142
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 18 publications
7
142
2
1
Order By: Relevance
“…Furthermore, these ER binding values for methoxychlor and HPTE correspond closely to previous determinations (43,63,64). The estrogenic pesticide kepone (10,11,24) had an hrER-a RBA value in the FP assay that is similar to the ER binding interactions reported from other laboratories (43,63). At the same time, the pesticide dieldrin was found to have only the extremely weak interaction with hrER-a that has been reported by others (66,70 CRBA values prefaced were calculated from IC50 values that we estimated from the cited literature.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, these ER binding values for methoxychlor and HPTE correspond closely to previous determinations (43,63,64). The estrogenic pesticide kepone (10,11,24) had an hrER-a RBA value in the FP assay that is similar to the ER binding interactions reported from other laboratories (43,63). At the same time, the pesticide dieldrin was found to have only the extremely weak interaction with hrER-a that has been reported by others (66,70 CRBA values prefaced were calculated from IC50 values that we estimated from the cited literature.…”
supporting
confidence: 89%
“…In the case of the estrogenic pesticide methoxychlor (12,25), this parent compound was found to have a much lower hrER-a RBA using the FP assay than its estrogenic metabolite HPTE. Furthermore, these ER binding values for methoxychlor and HPTE correspond closely to previous determinations (43,63,64). The estrogenic pesticide kepone (10,11,24) had an hrER-a RBA value in the FP assay that is similar to the ER binding interactions reported from other laboratories (43,63).…”
supporting
confidence: 87%
“…Quantitative structure-activity relationship (QSAR) models and qualitative SAR approaches have had some success in identifying and depicting structural features that contribute to the ability of a chemical to interact with steroid hormones, for both the estrogen receptor (ER) (Anstead et al 1997;Fang et al 2001;McKinney and Waller 1994;Tong et al 1997aTong et al , 1997bTong et al , 1998Waller et al 1996b;Wiese and Brooks 1994) and the AR (Loughney and Schwender 1992;Mekenyan et al 1997;Singh et al 2000;Tucker et al 1988;Waller et al 1996a). In the case of environmentally occurring chemicals, studies have revealed a common pattern of steric and electronic features involved in molecular recognition and receptor binding affinity, in spite of the molecular diversity of such data sets.…”
mentioning
confidence: 99%
“…[24][25][26] Attempts range from the use of simple two-dimensional 27) graph theoretical parameters and semiemperical quantum chemical methods 28) to highly sophisticated three dimensional (3D) approaches. [29][30][31][32][33][34] Structurally diverse 60 environmental estrogens 27) are classified through QSAR studies. Groups of aro-matic, phenolic and aliphatic tetra substituted pyrazole, 35) raloxifene 36) and xenoestrogens are modeled for studying the SAR for binding affinity to the ER.…”
mentioning
confidence: 99%